2023
DOI: 10.3390/foods12132540
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of (Poly)phenol Intake in Saliva Proteome: Short- and Medium-Term Effects of Apple

Abstract: The relationship between salivary proteome and dietary habits was studied in previous works, where a relationship between salivary proteins like cystatins and polyphenol/tannin levels in diet was observed. However, it remains to be elucidated if this association results from an effect of polyphenol-rich food ingestion on saliva composition. The aim of this work was to test the effects of apple intake on the saliva proteome, both in the short and medium term (after 4 days of continuous intake). By incubating sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…Here, although we cannot conclude whether amylase is bound to or not to apple polyphenols in supernatants, we show at least that it is only moderately precipitated. These results are in agreement with those of Louro et al, who used a protocol very similar to the one used in the present study. The authors reported that an apple polyphenol extract could precipitate amylase, but in fact, the results presented clearly show that amylase was present in much lower quantities in pellets than in supernatants.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Here, although we cannot conclude whether amylase is bound to or not to apple polyphenols in supernatants, we show at least that it is only moderately precipitated. These results are in agreement with those of Louro et al, who used a protocol very similar to the one used in the present study. The authors reported that an apple polyphenol extract could precipitate amylase, but in fact, the results presented clearly show that amylase was present in much lower quantities in pellets than in supernatants.…”
Section: Discussionsupporting
confidence: 94%
“…The first result that was expected is the dose-dependent precipitation of PRP in the band at 27 kDa. This finding is in perfect agreement with another study which also described the concomitant increase in pellets and decrease in supernatants of a 27.5 kDa band after the interaction of whole saliva with an apple polyphenolic extract. The authors proposed that this band contained igκ chain C and PRP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation